Filtry piaskowe jako element zintegrowanej ochrony materiału rozmnożeniowego w szkółkach leśnych - Oszako, Tomasz; Kubiak, Katarzyna; Nowakowska, Justyna; Siebyła, Marta (Leśne Prace Badawcze, 2013)
Slow Sand Filters (SSF) are a biological method used to protect nursery plants, from pathogen infections which can cause serious diseases in many forest tree species. Thanks to SSF application the number of phytopathogens in nurseries can be significantly reduced, as demonstrated by many field and greenhouse experiments (e.g. in Polish nurseries, and for horticultural crops in Germany and The Netherlands). In this study, the effect of pollution from fertilizers and fungicides used in agriculture (e.g. PCNB) on the efficiency of SSFs was assessed. A quantitative analysis was performed of the copiotrophic and oligotrophic bacterial composition colonizing SSF biofilms. The efficiency with which selected Oomycete strains belonging to the genus Phytophthora ( P. alni , P. cactorum , P. plurivora ) were removed from water was determined based on genetic material (DNA of the organisms) found in the SSF filtrate. Specific primers and TaqMan probes (qPCR) appeared to be the most sensitive molecular methods. Moreover, the microbiological analysis of SSF biofilm performed with selective media allowed the growth of copiothrophic and oligothrophic bacteria to be estimated. The influence of fungicide (PCNB) and N-fertilizer on the number of bacteria in each biofilm was also evaluated. The pollution of water with fertilizer (being used for plant irrigation) was demonstrated to reduce the efficiency of filtration more than fungicide addition (the amount of DNA from those investigated pathogens in the water decreased with time). The amount of bacteria in SSF biofilm readily increased after application of N-fertilizer in contrast to fungicide (PCNB) addition.